Is serum amylase normal in women with polycystic ovarian syndrome? (Baghdad Science Journal, 2014)
Background : Polycystic ovary syndrome (PCOS) is the most common cause of infertility in reproductive-age women , it is an important harbinger of metabolic disorders. It has been reported that hyperamylasemia can be used as marker of ovarian cancer patients . The current study was conducted to evaluate amylase activity and to estimate the correlation of this enzyme with insulin and insulin resistance in PCOS patients.Methods: This study was conducted on forty five patients with PCOS in comparison to twenty five women as control. Fasting blood sample was taken from each subject and analyzed for amylase activity , FSH,LH, Insulin , proteins, and blood sugar , meanwhile insulin resistance was determined by HOMA-IR index. Results: The results of the study showed a significant increase (p